1995
DOI: 10.1093/ndt/10.supp2.69
|View full text |Cite
|
Sign up to set email alerts
|

Chairman's Workshop Report: R-HuEPO hyporesponsiveness--who and why?

Abstract: The most common cause of limited response to recombinant human erythropoietin (r-HuEPO) is unrecognized, mild-to-moderate iron deficiency, either at the start of treatment or secondary to enhanced iron utilization by newly formed erythrocytes. Iron stores in patients with chronic renal failure (CRF) are often depleted through gastrointestinal bleeding, blood loss during haemodialysis, and blood sampling. Mobilization of iron stores may be inadequate, especially during rapid haemoglobin regeneration. Aluminium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…Previous reports have also indicated that a major ABO mismatch does not prevent appropriate response to rHuEPO [41]. Because of the major inflammatory response they elicit, infections often result in a delay or loss of response to rHuEPO therapy in other settings [14,17,42], but not in our NMSCT patients. The use of an unrelated donor increases the risk of infection as well as of acute GVHD, a complication associated with further inhibition of endogenous EPO production [16,17,43] and a cytokine storm potentially inhibiting marrow erythropoiesis [44], but this did not prevent response to rHuEPO in our patients.…”
Section: Weeks After Nmsctmentioning
confidence: 74%
“…Previous reports have also indicated that a major ABO mismatch does not prevent appropriate response to rHuEPO [41]. Because of the major inflammatory response they elicit, infections often result in a delay or loss of response to rHuEPO therapy in other settings [14,17,42], but not in our NMSCT patients. The use of an unrelated donor increases the risk of infection as well as of acute GVHD, a complication associated with further inhibition of endogenous EPO production [16,17,43] and a cytokine storm potentially inhibiting marrow erythropoiesis [44], but this did not prevent response to rHuEPO in our patients.…”
Section: Weeks After Nmsctmentioning
confidence: 74%
“…Chronic inflammation can modify the process of erythropoiesis, probably via various inflammatory cytokines (Danielson, 1995;Cooper et al, 2003). Pro-inflammatory cytokines, which are under some degree of genetic control, may be associated with EPO resistance.…”
Section: Introductionmentioning
confidence: 99%
“…However, a considerable amount of patients do not respond well to rhEPO therapy and the most common cause of this is inadequate supply of iron needed for erythropoiesis [6]. Intravenous (i.v.)…”
Section: Introductionmentioning
confidence: 99%